Effect of feeding garlic leaves on rumen fermentation, methane emission, plasma glucose kinetics, and nitrogen utilization in sheep - Panthee, Arvinda (J Anim Sci Technol, 2017)
BACKGROUND: Garlic and its constituents are reported to have been effective in reducing methane emission and also influence glucose metabolism in body; however, studies in ruminants using garlic leaves are scarce. Garlic leaves contain similar compounds as garlic bulbs, but are discarded in field after garlic bulb harvest. We speculate that feeding garlic leaves might show similar effect as garlic constituents in sheep and could be potential animal feed supplement. Thus, we examined the effect of freeze dried garlic leaves (FDGL) on rumen fermentation, methane emission, plasma glucose kinetics and nitrogen utilization in sheep. METHODS: Six sheep were fed Control diet (mixed hay and concentrate (60:40)) or FDGL diet (Control diet supplemented with FDGL at 2.5 g/kg BW(0.75) of sheep) using a crossover design. Methane gas emission was measured using open-circuit respiratory chamber. Plasma glucose turnover rate was measured using isotope dilution technique of [U-(13)C]glucose. Rumen fluid, feces and urine were collected to measure rumen fermentation characteristics and nitrogen utilization. RESULT: No significant difference in rumen fermentation parameters was noticed except for rumen ammonia tended to be higher (0.05 < P < 0.1) in FDGL diet. Methane emission per kg dry matter ingested and methane emission per kg dry matter digested were lower (P < 0.05) in FDGL diet. Plasma glucose concentration was similar between diets and plasma glucose turnover rate tended to be higher in FDGL diet (0.05 < P < 0.1). Nitrogen retention was higher (P < 0.05) and microbial nitrogen supply tended to be higher (0.05 < P < 0.1) in FDGL diet. CONCLUSION: FDGL diet did not impair rumen fermentation, improved nitrogen retention; while absence of significant results in reduction of methane emission, glucose turnover rate and microbial nitrogen supply, further studies at higher dose would be necessary to conclude the merit of FDGL as supplement in ruminant feedstuff.